Plasticity and Awareness of Bodily Distortion - Mariella Pazzaglia; Marta Zantedeschi (Neural Plasticity)
Knowledge of the body is filtered by perceptual information, recalibrated through predominantly innate stored information, and neurally mediated by direct sensory motor information. Despite multiple sources, the immediate prediction, construction, and evaluation of one’s body are distorted. The origins of such distortions are unclear. In this review, we consider three possible sources of awareness that inform body distortion. First, the precision in the body metric may be based on the sight and positioning sense of a particular body segment. This view provides information on the dual nature of body representation, the reliability of a conscious body image, and implicit alterations in the metrics and positional correspondence of body parts. Second, body awareness may reflect an innate organizational experience of unity and continuity in the brain, with no strong isomorphism to body morphology. Third, body awareness may be based on efferent/afferent neural signals, suggesting that major body distortions may result from changes in neural sensorimotor experiences. All these views can be supported empirically, suggesting that body awareness is synthesized from multimodal integration and the temporal constancy of multiple body representations. For each of these views, we briefly discuss abnormalities and therapeutic strategies for correcting the bodily distortions in various clinical disorders.